Assessment of Aahper Youth Fitness Norm: Sri Lankan (North Province) Adolescents Boys - Ketheeswaran, K.; Gopinath, V. (Sharirik Shiksha Unnayan Sansthan, 2012)
The aim of the study was to compare and evaluate the AAPHER youth fitness test among north province adolescent boys in Sri Lanka. To achieve the purpose (N=800) adolescent boys from age of 14 years (n=400) and 15 years (n=400) were randomly selected as subjects from north province, Sri Lanka AAPHER (50 yards – speed, Standing broad jump – explosive power, 1.5 miles run – endurance, situps – abdominal strength, shuttle run – agility and pullups-arm strength) youth fitness test were selected as criterian, variable tested, the data were converted into AAPHER youth fitness norms. The result of AAPHER youth fitness existing norms shows that, 14 and 15 years boys of north province were mostly below the 50th percentile in all the fitness qualities. From the result it was concluded that the adolescent boys of north province (Sri Lanka) were having poor physical fitness. The pupil scored below 50 decileson the selected fitness variable in their respective age group should be encouraged to improve their fitness level. National level special fitness programme will be designed and implemented to the poor fitness students. Further national level common fitness norms may be constructed and standardized for fitness assessment.
Keywords: AAPHER; Fitness; Norms; Adolescent